Port economics, management and policy - Notteboom, Theo; Pallis, Athanasios A.; Rodrigue, Jean-Paul 1967- (Routledge, 2022)
Port Economics, Management and Policy provides a comprehensive analysis of the contemporary port industry, showing how ports are organized to serve the global economy and support regional and local development. Structured in nine sections, this textbook examines a wide range of seaport topics, covering maritime shipping and international trade, port terminals, port governance, port competition, port policy and much more. Key features of the book include its: Multidisciplinary perspective, drawing on economics, geography, management science and engineering Multisector analysis including containers, bulk, break-bulk and the cruise industry Focus on the latest industry trends, such as supply chain management, automation, digitalization and sustainability Benefitting from the authors' extensive involvement in shaping the port sector across five continents, this text provides students and scholars with a valuable resource on ports and maritime transport systems. Practitioners and policymakers can also use this as an essential guide towards better port management and governance.